Effect of heat shock protein 90 against ROS-induced phospholipid oxidation. (1st February 2018) - Zhang, Muhan; Wang, Daoying; Geng, Zhiming; Li, Pengpeng; Sun, Zhilan; Xu, Weimin
Highlights: Hsp90 from duck muscle could inhibit H2 O2 induced lipid oxidation. The bacteria containing Hsp90 showed more survival and better membrane integrity. Hsp90 is an inherent antioxidant and have potential use in meat products. Abstract: The antioxidative role of Hsp90 purified from duck muscle on phospholipid was investigated in this study. Lipid oxidation was assessed by ferric thiocyanate method, and particle size, zeta potential measurements and transmission electron microscopy were employed to detect physical and chemical changes during oxidation of liposomes. Increase of the peroxidation products, decrease of the particle size and disruption of the spherical unity of the liposomes were detected when liposome was exposed to hydrogen peroxide (H2 O2 ) oxidation, and Hsp90 was shown to protect liposome against oxidation. To further test the protection of Hsp90 on cell membrane, the Hsp90 transformed E. coli cell model was built. The Hsp90-containing E. coli showed higher survival and better membrane integrity as compared to the control upon H2 O2 exposure. It is expected that Hsp90 plays an important role in the prevention of phospholipids oxidation in meat and has potential use as a food antioxidant.